Benthic foraminifera counts in sediment cores CE18011_VC1 and RH17002_VC7 - O'Reilly, Luke (In: O'Reilly, L (2022): Coral content, radiocarbon dating, geochemistry, benthic foraminifera and grain size distribution in sediment cores CE18011_VC1 and RH17002_VC7 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.945476, 2022)
A remotely operated vehicle mounted (ROV) vibrocorer rig acquired the two cores from the Porcupine Bank Canyon (NE Atlantic) and western Porcupine Bank (NE Atlantic) during the RH17002 and CE18011 research cruises. RH17002_VC7 is a 0.81 m ROV-vibrocore and was acquired from a cold-water coral mound summit on lip of the Porcupine Bank Canyon. CE18011_VC1 is a 1.30 m ROV-vibrocore and was acquired from cold-water coral mound summit on the western Porcupine Bank. Benthic foraminifera assemblages were analysed from both cores. Their abundances were used to infer paleoenvironmental signals between 9.1 to 5.6 ka BP, and used concurrently with coral content percentages derived from computer tomography. The data was collected by identifying and counting benthic foraminifera from the >125 µm fraction of sediment from the cores.
Keywords: Benthic foraminifera; cold-water coral mound; NE Atlantic